2016
DOI: 10.1177/1359105316631813
|View full text |Cite
|
Sign up to set email alerts
|

The interactive effects of patient control beliefs on adherence to fluid-intake restrictions in hemodialysis: Results from a randomized controlled trial

Abstract: This study examined the interactive role of perceived control and preference for control on adherence in a sample of patients with chronic kidney disease. As part of a randomized controlled trial assessing adherence to fluid-intake restrictions, 119 hemodialysis patients completed measures of these constructs; results indicated that patients with high perceived control and high preference for control demonstrated the most favorable adherence. This suggests that patients who believe health-related outcomes are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…No differences regarding adherence to antihypertensive or PO 4 lowering medication and the psychological variables measured were observed. A more recent study provides important findings around perceived (“Internal”) control and adherence to fluid restriction (Howren et al, 2016a). This study examined patients participating in a randomized trial of behavioral self-regulation in 119 HD patients who were not fluid adherent.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…No differences regarding adherence to antihypertensive or PO 4 lowering medication and the psychological variables measured were observed. A more recent study provides important findings around perceived (“Internal”) control and adherence to fluid restriction (Howren et al, 2016a). This study examined patients participating in a randomized trial of behavioral self-regulation in 119 HD patients who were not fluid adherent.…”
Section: Discussionmentioning
confidence: 99%
“…The recent study (Howren et al, 2016a) of fluid adherence suggests that those patients who believe health-related outcomes are a function of their own behaviors and that they have the opportunity to exert control could be most adherent to complex regimes. But the difficulty remains – how to influence and modulate behavior with interventions in patients with a wide range of beliefs about perceived locus of control.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies found that the factors affecting fluid restriction in HD patients include age, sex, lack of knowledge, family support, thirst, and dietary salt intake (Gibson et al, 2016; Howren et al, 2017). Furthermore, factors such as high-sodium content in processed foods, social and cultural backgrounds, and policy support have also been related to fluid management of patients with CKD (Bossola et al, 2018; Hong et al, 2017; Y.…”
Section: Introductionmentioning
confidence: 99%
“…Some women would prefer to have decisions made by competent medical professionals. It is actually the mismatch between desire for control and actual perceived control over healthcare processes that can result in poorer health outcomes (Arora, Weaver, Clayman, Oakley-Girvan, & Potosky, 2009;Benyamini, Nouman, & Alkalay, 2016;Christensen et al, 2010;Howren, Cozad, & Christensen, 2017;Wallston et al, 1987). Understanding the role of perceived control requires application of a person-environment fit model such that the degree of "fit" between women's desire for control of healthcare processes during childbirth and the extent to which those desires were matched by experience is directly related to optimal maternal health outcomes (Reich, Zautra, & Manne, 1993).…”
mentioning
confidence: 99%